Effects of a proximity-sensing feedback chair on head, shoulder, and trunk postures when working at a visual display terminal. - Yoo W; Yi C; Kim M (Journal of Occupational Rehabilitation, 2006)
Introduction: This study was designed to identify the effects of feedback from a proximity-sensing chair on head, shoulder, and trunk postures when working at a visual display terminal (VDT). Methods: Twenty healthy adults were asked to perform VDT work, and their forward head, forward shoulder, and trunk flexion angles were analyzed using a 3-D motion analysis system. The statistical significance of differences between without and with an auditory feedback device was tested by paired t-tests, with the significance cutoff set at [alpha]=0.05. Results: The forward head, forward shoulder, and trunk flexion angles significantly decreased during VDT work when using the proximity sensor with auditory feedback. Conclusion: We suggest that a feedback device promotes the adoption of beneficial postures, which may be effective in preventing VDT-work-related neck and upper-limb disorders.